Stomata dan Trikoma Kultivar Kedelai Anjasmoro selama pemupukan Nanosilika dan Plant Growth Promoting Rhizobacteria - Sri Suryanti; Arif Umami (Vegetalika, 2020)
Soybean is a very important crop commodity in Indonesia. Increasing soybean production on dryland as cultivation land need to be carried out. Dryland have issues with either of nutrient and water availability which is not supportable for plant growth. Therefore, the application of nano-silica and plant growth promoting rhizobacteria (PGPR) are expected to increase nutrient absorption, synthesis of plant growth hormone and increase in plant resistance to drought stress. The growth of drought-resistant plants is able to be showed through the status of stomata and trichomes on leaves. So that, this study aimed to determine the stomata and trichome performance of soybean plants of Anjasmoro cultivar using nano-silica and PGPR as fertilizers. The study design used a completely randomized design with 2 factors with three replication. The first factor was nano silica concentration i.e. 0, 100 and 200 ppm. The second factor was PGPR concentration i.e. 0, 5, 10, and 15%. Results showed that the nanosilica and PGPR applications had no significant effect on stomata and trichome status of Anjasmoro cultivar except for stomatal aperture and the ratio of the size of the stomata openings. A positive correlation has been found in the study between stomata openings and soybean yields.